Analysis of the Effect of Inflation and Investment on Unemployment in Yogyakarta in 2019-2023 - Anindita, Reva Tri; Putra, Arul Ramanda; Rohimallah, Hafidz Muharrom; Desmawan, Deris (LPPPIPublishing, 2024)
Unemployment is a term given to people who are not working at all or people who are looking for work. Unemployment occurs in many regions, including the Special Region of Yogyakarta. Unemployment is an economic problem, because unemployment reduces the level of productivity and income of the community, which results in poverty and social problems. Unemployment is caused by the size of the labour force that is not balanced with employment opportunities. This causes intense competition, because there are not many job opportunities available in the region or country. The purpose of this study is to determine the effect of inflation and investment on unemployment in the Special Region of Yogyakarta in 2019-2023. Researchers used secondary data for their research. Multiple regression analysis of this study. The results of the research in D.I Yogyakarta in 2019-2023: 1. Inflation on unemployment has no significant influence on unemployment. 2. Investment has a significant influence on unemployment 3. Simultaneously, inflation and investment have no influence on unemployment. This shows that high unemployment costs lead to reduced productivity, community income and economic growth.